2019
DOI: 10.1002/cctc.201900500
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐Stability Volcano Plots for Material Optimization in Electrocatalysis

Abstract: In the last two decades, research in electrocatalysis has been spurred by theoretical calculations and predictions based on the concept of ab initio thermodynamics, which has become a valuable tool for computational researchers in material screening. These investigations most commonly result into the construction of activity‐based volcano plots in order to predict potential electrocatalysts for the application in practice. However, the prototypical activity‐based volcano concept neither captures the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 77 publications
(252 reference statements)
0
24
0
Order By: Relevance
“…The presented strategy constitutes an alternative to conventional material screening methods in the literature and extends the previous work of the author to develop material screening approaches beyond the traditional Volcano analysis in electrocatalysis. [94][95][96] The main advantage of the outlined procedure constitutes the fact that the kinetics of the CER and OER is accounted for, whereas conventional material screening techniques rely on thermodynamic considerations only. It is suggested to employ the free energy difference of the limiting OOH and OCl adsorbate, i. e., ΔG(OOH)-ΔG(OCl) (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The presented strategy constitutes an alternative to conventional material screening methods in the literature and extends the previous work of the author to develop material screening approaches beyond the traditional Volcano analysis in electrocatalysis. [94][95][96] The main advantage of the outlined procedure constitutes the fact that the kinetics of the CER and OER is accounted for, whereas conventional material screening techniques rely on thermodynamic considerations only. It is suggested to employ the free energy difference of the limiting OOH and OCl adsorbate, i. e., ΔG(OOH)-ΔG(OCl) (cf.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is questionable, whether Δ E O is a suitable choice to describe the selectivity problem of the competing CER and OER adequately. In case of the CER, the usage of Δ E O appears justified, since for transition‐metal oxides, such as RuO 2 and IrO 2 , it has been shown that oxygen atoms in junction with the underlying metal atom (Me) serve as active sites for electrochemical chlorine formation: the adsorption and discharge of a chloride anion from the electrolyte solution results in the formation of an OCl adsorbate, reconciled as precursor for the formation of gaseous chlorine (cf. equation ). trueMe-normalO+Cl-Me-OCl+normale-1.em0.166667em0.277778em(ΔGOCl) …”
Section: Introductionmentioning
confidence: 99%
“…After the most active materials have been determined by the conventional volcano framework or the concept of ESSI-descriptor activity maps, activity-stability volcano curves for these catalysts are constructed to assess the interrelationship between activity and stability in dependence of the applied overpotential. [107] Therefore, an ultimate task for computational researchers is to elaborate material-screening techniques that include catalyst stability directly (a priori) in its framework. It would be desirable if it becomes feasible to screen electrodes in a homologous series of materials, differentiating between active and inactive catalysts, but at the same time also to sort the most active materials into potentially stable or unstable.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…[ 106 ] First steps toward this notion have been made by constructing volcano curves based on the assessment of linear scaling relationships for the electrocatalytic activity and catalyst stability, resulting in the construction of activity‐stability volcano plots. [ 107 ] The underlying approach, originally developed for the assessment of electrode materials in lithium‐ion batteries, [ 108 ] does not allow screening electrodes in a homologous series of materials, but instead enables optimization of selected electrocatalysts toward the best compromise between activity and stability. Therefore, the aspect of catalyst stability within trend studies can only be addressed a posteriori.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation